Investigation and Management of Stool Frequency and Consistency Associated With SGLT1 Inhibition by Reducing Dietary Carbohydrate: A Randomized Trial. Issue 5 (29th April 2020) - He, YanLing; Schofield, Jül; Mahling, Ping; Mendonza, Anisha E.; Hinder, Markus
Abstract : Treatment with licogliflozin, a dual sodium‐glucose co‐transporter (SGLT)1/2‐inhibitor, is associated with increased stool frequency and loose stools, attributed to SGLT1 inhibition. To investigate the effect of carbohydrate content and supplements on licogliflozin‐induced stools, a randomized, open‐label, two‐part ( N = 24/part), three‐period crossover study was carried out in overweight or obese adults. Significantly higher ( P < 0.01) change from baseline in 3‐day total number of bowel movements was observed following 3 days of licogliflozin treatment (50 mg q.d.) together with a 50% carbohydrate meal compared with a 25% and 0% carbohydrate meal. The number of stools with Bristol Stool Chart score of 6 or 7 was also significantly lower following a 0% carbohydrate meal. Supplementation with psyllium 6 g or calcium carbonate 1 g had no effect on stool changes following treatment. Licogliflozin was generally safe and well‐tolerated. Loose stool associated with licogliflozin treatment and ingestion of meals can be managed by reducing the carbohydrate content of meals taken with licogliflozin.